Gender-specific differences in the kinetics of nonfasting TRL, IDL, and LDL apolipoprotein B-100 in men and premenopausal women - Matthan, Nirupa R; Jalbert, Susan M; Barrett, P Hugh R; Dolnikowski, Gregory G; Schaefer, Ernst J; Lichtenstein, Alice H (Arteriosclerosis, thrombosis, and vascular biology, 2008)
To investigate mechanisms underlying gender differences in serum lipoprotein concentrations, the kinetic behavior of apoB-100 was assessed. Twenty subjects (<50 years; 12 men and 8 premenopausal women) were provided a Western diet for 4 to 6 weeks, after which the kinetics of apoB-100 in triglyceride-rich, intermediate-density, and low-density lipoprotein (TRL, IDL, and LDL) were determined in the fed state. Nonfasting plasma TC, LDL-C, and triglyceride concentrations were 23%, 34%, and 57% lower, respectively, in the women compared with men. Plasma TRL and LDL apoB 100 pool sizes were lower by 40% and 30%, respectively. These differences were accounted for by higher TRL and LDL apoB 100 fractional catabolic rates (FCR), rather than differences in production rates (PR). Plasma TRL-C and LDL-C were positively correlated with TRL and LDL apoB 100 concentrations and pool size, and negatively correlated with TRL and LDL apoB 100 FCR (women: r=-0.59, P<0.01 and r=-0.54, P<0.04, and men: r=-0.43, P<0.05 and r=-0.44, P<0.05). No significant associations were observed between plasma TRL-C and LDL-C and PR. These data suggest the mechanism for lower TRL-C and LDL-C concentrations in women was determined predominantly by higher TRL and LDL FCR rather than lower PR. This could explain, in part, the lower CVD risk in premenopausal women relative to men.